MAGNETO-SEISMIC INTERPRETATION OF SUBSURFACE VOLCANISM IN THE GAETA GULF (ITALY, TYRRHENIAN SEA) - de Alteriis G.; Passaro S.; Fedi M.; Siniscalchi A. (My University, 2006)
The occurrence of a former subaerial volcanic edifice off the Volturno River (Tyrrhenian Sea, Gulf of Gaeta) in the 41°N parallel is suggested by joint interpretation of multichannel seismic lines and ship-borne magnetic data. In the Campanian region igneous (volcanic) rocks are very close to the carbonate Mesozoic basement and seismics cannot always discriminate between them. A joint seismic-magnetic analysis was very effective in assessing the lithological nature of the bodies evidenced by both geophysical methods. Distortion analysis showed that the main magnetic source in the area is characterised by a not normal-polarity direction of the magnetization, similar to other Pleistocene volcanoes in the Tyrrhenian region. Hence we argued that the overall magmatic emplacement for this source occurred during a reverse-polarity chron, very likely the 0.78-1.78 Ma time span. This magnetically-derived time constraint is in agreement with seismic stratigraphy that shows that the entire volcano is sealed by the Volturno River prograding delta from Middle Pleistocene to Present in age. Our interpreted volcano belongs to a set of inferred onshore and offshore volcanic edifices all lying along the 41°N parallel.
Keywords: 41°N PARALLEL; BURIED VOLCANISM; GAETA GULF; INVERTED MAGNETIC ANOMALIES; REFLECTION SEISMICS; Кайнозой::Четвертичная::Плейстоцен; Мезозой::Меловая::Верхний::Кампанский; Cenozoic::Quaternary::Pleistocene; Mesozoic::Cretaceous::Upper::Campanian